SEMIOLOGY OF FOLK TALES OF VILLAGES IN SIDOARJO AS THE SPIRIT OF CULTURAL EDUCATION FOR THE INDONESIAN GENERATION - Susilo, Joko; Mandarani, Vidya; Junaedi, Muhammad; Tirtoni, Feri; Suwarta, Nyoman (JURNAL LITERASI, 2024)
Folklore from villages in Sidoarjo has the potential to become a rich object of cultural knowledge. The villages in Sidoarjo have various origin stories. These stories are related to past events, from the Kahuripan period, Majapahit, the arrival of Islam, to the colonial period. Many of the origin stories of villages or hamlets in Sidoarjo are still raw and have not been explored for their meaning, nor have they been explored to become serious cultural objects, to strengthen Sidoarjo's cultural identity, to become cultural knowledge for generations, or to become objects of creating works of art. This research work gradually collects the origin stories of the villages in Sidoarjo and interprets the content of the stories contained therein. The theory and method of Roland Barthes's semiology are used as a means of meaning. In this session, 4 (four) villages that had story relationships were studied, those are: Candi Village, Entalsewu Village, Tangkil Village, and Sumput Village. The stories of the origins of the four villages contain symbols of human life behavior that strive to build an independent society, set an example of independence, and awaken a sense of love for the motherland.